Abundance study of fish species from Hel River of Kokrajhar, Assam, India - Arjina Parbin Sarkar; Sandeep Das; Sanjay Basumatary (Journal of Fisheries, 2022)
Hel River is an important river of Kokrajhar district of Assam, India, which is a great source of freshwater fish. Considering the availability of indigenous fish species in Hel River and consumption of these species by the local people, the prime objective of this study was to study the fishes in the river. The relative abundance of fishes along with the species richness and species evenness were calculated based on fish samplings from August 2014 to July 2015. A total of 1313 individuals belonging to 25 species were recorded, dominated by family Cyprinidae with nine species. The highest relative abundance was recorded for Barilius bendelisis (15.31%) followed by Garra gotyla (14.09%) and Barilius barna (13.78%). This study may serve as an important baseline for sustainable management of Hel River.